2016
DOI: 10.1080/24748668.2016.11868929
|View full text |Cite
|
Sign up to set email alerts
|

Static balance and dynamic balance related to rotational movement in ballet dance students

Abstract: The aim of this study was to assess static and dynamic balance related to rotational movements en pointe and en demi pointe in ballet dance students. The study group consisted of 13 people -students of one of the ballet schools in Poland: 9 dancers from the junior class (14 years old) and 4 dancers form the senior class (18 years old). For the purpose of statistical analysis, the group was divided into 4 subgroups. Each person took part in a static balance test which included a 30s trial with eyes opened and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This suggested that the lack of visual feedback increased the imbalance after the dance sessions. The results of the present study corresponded to the results of the study of Fronczek-Wojciechowska et al [15]. The other examined COP parameters did not show a significant difference at the 95% confidence level, which can be explained by the dancers' experience as their bodies are accustomed to dancing later in the repetitions.…”
Section: Discussion Of the Balance Test Datasupporting
confidence: 90%
See 2 more Smart Citations
“…This suggested that the lack of visual feedback increased the imbalance after the dance sessions. The results of the present study corresponded to the results of the study of Fronczek-Wojciechowska et al [15]. The other examined COP parameters did not show a significant difference at the 95% confidence level, which can be explained by the dancers' experience as their bodies are accustomed to dancing later in the repetitions.…”
Section: Discussion Of the Balance Test Datasupporting
confidence: 90%
“…Besides dynamic motion analysis, assessment of dancers' static balancing ability is also an extremely important field to analyze [13][14][15]. According to the literature review of da Silveira Costa et al, the aims of static balance tests in dancers are focused on three different fields: comparison of balancing skills in dancers and nondancers, examining balancing ability according to dance knowledge, and the examination of the effect of visual feedback on balancing ability [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal interaction between the vestibular, proprioceptive and visual systems conditions the performance associated with balance, which may be affected by aging [5,10,11,12]. The values of the balance evaluated with the eyes open are higher than the ones evaluated with the eyes closed, aspect confirmed by the testing of the Polish ballerinas, at which better performances are signalled with increasing age, those aged 18 years old having higher results than puberty 14 years old [13]. Postural stability also depends on the information provided PEDAGOGY by the cervical proprioceptors, whose feedback improves the balance on the non-dominant leg of Taekwondo fighters, compared to untrained people [14].…”
mentioning
confidence: 83%
“…Maintaining dynamic balance performances are significantly improved by the presence of visual feedback [5]. Poor ballet dancers in Poland show poor performance of static and dynamic balance with their eyes closed [6]. For young women in Poland (18-28 years old), the use of shoes with high heel/heel height (especially 10 cm), combined with the exclusion of visual function, generates a limitation of the values of static balance [7].…”
Section: Introduction 1factors Influencing the Manifestation Of Balancementioning
confidence: 99%